2021
DOI: 10.1371/journal.pcbi.1009008
|View full text |Cite
|
Sign up to set email alerts
|

A modular approach for modeling the cell cycle based on functional response curves

Abstract: Modeling biochemical reactions by means of differential equations often results in systems with a large number of variables and parameters. As this might complicate the interpretation and generalization of the obtained results, it is often desirable to reduce the complexity of the model. One way to accomplish this is by replacing the detailed reaction mechanisms of certain modules in the model by a mathematical expression that qualitatively describes the dynamical behavior of these modules. Such an approach ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 114 publications
(171 reference statements)
2
21
0
Order By: Relevance
“…In what follows, we will introduce and elaborately study the dynamics of different oscillator models built on each of the bistable switches in Figure 1, as well as both switches combined. Note that we introduced a similar approach in De Boeck et al (2021), which allowed for greater control over the response curve. However, here we limit ourselves to a cubic nonlinear function as it is likely one of the simplest expressions that can be used to reproduce a bistable switch.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In what follows, we will introduce and elaborately study the dynamics of different oscillator models built on each of the bistable switches in Figure 1, as well as both switches combined. Note that we introduced a similar approach in De Boeck et al (2021), which allowed for greater control over the response curve. However, here we limit ourselves to a cubic nonlinear function as it is likely one of the simplest expressions that can be used to reproduce a bistable switch.…”
Section: Resultsmentioning
confidence: 99%
“…This triggers the question of what the advantage might be of interlinking bistable switches to generate cell cycle oscillations when combined with negative feedback? We recently found that having multiple bistable switches can increase the parameter range of oscillations, while also allowing to switch between regions of qualitatively different oscillations (in terms of period and amplitude) De Boeck et al (2021). Having multiple positive feedback loops (which can lead to bistability) has been shown to allow for improving speed and resistance to noise Brandman et al (2005), which could also indicate a potential advantage of interlinked bistable switches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 ( ! , which was used to describe the ultrasensitive response previously 44,47 . We set đŸ : = 400 and 𝑛 = 70…”
Section: Methods Detailsmentioning
confidence: 99%
“…After the arrival at the perinucleus, 𝑅 " undergoes phosphorylation with one of the three phosphorylation mechanisms (Figure 2A) and enters the nucleus. To describe these different types of phosphorylation, we adopted the modular approach, which describes complex multistep reactions with a single phenomenological module that qualitatively describes the dynamical behavior 47,52 . This allowed us to simulate the complex phosphorylation process, which is a necessary step for nuclear entry (see STAR Methods).…”
Section: Bistable Phosphorylation Of Per Allows Sharp Transcriptional...mentioning
confidence: 99%